Economic Rational Analysis of Early Marriage Behavior of Transmigration Families in Mamuju Tengah Regency - Marsadi. H; St. Nurhayati; Damirah Damirah; Muzdalifah Muhammadun; Andi Bahri (Jurnal Ilmu Manajemen Profitability, 2026)
Early marriage remains a persistent social and economic phenomenon in transmigration communities, particularly in rural areas where structural vulnerability, limited education, and economic hardship intersect. Despite extensive religious and legal debates, there is limited research examining early marriage through the lens of economic rationality within Islamic economic perspectives. This study aimed to analyze the rational economic considerations underlying early marriage behavior among transmigration families in Central Mamuju Regency. The research employed a qualitative case study design. The population consisted of transmigration community members in Karossa District, and participants were selected purposively based on their direct experience with early marriage cases. Primary data were collected through in-depth interviews, observation, and documentation, and were analyzed using thematic analysis with triangulation techniques to ensure validity. The findings indicated that early marriage was driven by interconnected factors, including economic pressure, low parental education, social media influence, peer association, and premarital pregnancy. Many parents perceived marriage as a rational strategy to reduce household economic burdens and secure their children’s livelihoods. However, the results showed that early marriage often produced adverse economic consequences, including unstable income, continued dependence on parents, increased household conflict, and vulnerability to poverty. From an Islamic economic perspective, the practice reflected short-term rational calculations rather than long-term welfare optimization (maslahah). This study contributes to the discourse on economic rationality in family decision-making and highlights the need for integrated policy interventions emphasizing education, economic empowerment, and preventive social programs to mitigate early marriage in vulnerable communities.